What do Spanish adolescents think about obsessive-compulsive disorder? Mental health literacy and stigma associated with symmetry/order and aggression-related symptoms. (April 2017) - García-Soriano, Gemma; Roncero, María
Abstract: Obsessive-compulsive disorder (OCD) is a frequent and disabling disorder with a long delay in seeking help that could partly be due to poor mental health literacy and stigmatizing attitudes. This study analyzes the mental health literacy and stigma associated with symmetry/order and aggression-related OCD in a Spanish adolescent sample. This age group was chosen because adolescence is a vulnerable period for the development of OCD, and adolescents are often reluctant to seek professional help. One hundred and two non-clinical adolescents read two vignettes describing symmetry/order and aggression-related OCD. Then, referring to these two vignettes, they answered questions related to problem recognition, causality perception, need for treatment, treatment recommendations, and stigma. Results show that a high percentage of adolescents recognize the interference of order- and aggression-related OCD, consider that a peer with order- or aggression-related OCD needs treatment, and would recommend a formal source of help. Although order symptoms are highly recognized as OCD by adolescents, aggression-related OCD is frequently misidentified as schizophrenia or depression. Results also show higher levels of stigmatizing attitudes in adolescents, associated with aggression-OCD (versus order-OCD), especially in male adolescents and adolescents with no previous experience with mental health services/providers. Results suggest the need to develop school-based programs emphasizing OCD content heterogeneity, especially the aggression, sexual, and religious contents, and work toward eliminating stigma. Highlights: Most Spanish adolescents (84.3%) recognize order-related OCD. Only 23.5% of Spanish adolescents (84.3%) recognize aggression-related OCD. Spanish adolescents (100–86.3%) would recommend formal help for aggression/order-OCD. Spanish adolescents show greater stigma toward aggression-OCD (versus order-OCD). Mental health services/providers' experience is associated with lower OCD-stigma.